Use of microwave technology in transdermal drug delivery / Nor Khaizan Anuar - Anuar, Nor Khaizan (Institute of Graduate Studies, UiTM, 2013)
The project focused on the use of microwave in controlling drug release from film matrix and modifying skin barrier for transdermal drug delivery. With reference to controlledrelease application, the effects of microwave on drug release properties of pectin films carrying sulfanilamide (P-SN), sulfathiazole (P-ST) and sulfamerazine (P-SM) of high to low aqueous solubilities were investigated. These films were prepared by solvent-evaporation technique and treated by microwave at 80 W for 5 to 40 min. Their profiles of drug dissolution, drug content, matrix interaction and matrix crystallinity were determined by drug dissolution testing, drug content assay, differential scanning calorimetry, X-ray diffractometry and scanning electron microscopy techniques. Microwave was found to be able to increase the matrix amorphousness. However, the strength of matrix interaction was accordingly increased thereby lowering the drug release propensity with a greater retardation extent in P-SN films. A gain in amorphous structure did not necessarily increase the drug release of film. Microwave can possibly retard drug release of pectin film carrying water-soluble drug through modulating its state of matrix interaction. In the case of skin barrier modification by microwave, the mechanism of microwave enhancing transdermal permeation of drug from film through its action on skin was investigated. The transdermal drug delivery profiles of pectin film was evaluated against pectin gel with reference to the influences of microwave, as well as chemical permeation enhancer namely oleic acid on skin. Hydrophilic P-SN films and gels, with or without oleic acid (OA), were prepared and subjected to drug release and skin permeation studies…